2014
DOI: 10.1007/s00018-014-1800-3
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular signaling mechanisms of the melanocortin receptors: current state of the art

Abstract: The melanocortin system is composed by the agonists adrenocorticotropic hormone and α, β and γ-melanocyte-stimulating hormone, and two naturally occurring antagonists, agouti and agouti-related protein. These ligands act by interaction with a family of five melanocortin receptors (MCRs), assisted by MCRs accessory proteins (MRAPs). MCRs stimulation activates different signaling pathways that mediate a diverse array of physiological processes, including pigmentation, energy metabolism, inflammation and exocrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 146 publications
1
49
0
Order By: Relevance
“…In fact, photoreceptor cell membranes are particularly rich in polyunsaturated fatty acids and extremely vulnerable to oxidative damage being the major site of superoxide generation in diabetes [34]. As MCR 1,5 modulate the nuclear transcription of the cAMP response element-binding protein (CREB) [17,35] and CREB as a redox-regulated pathway modulating MnSOD transcription [36], a possible theoretical frame, supporting this proposal, is that high-glucose exposure overexpresses MCR 1,5 and the addition of MCR 1,5 agonists lead to cAMP-PKA-CREB, increasing MnSOD transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, photoreceptor cell membranes are particularly rich in polyunsaturated fatty acids and extremely vulnerable to oxidative damage being the major site of superoxide generation in diabetes [34]. As MCR 1,5 modulate the nuclear transcription of the cAMP response element-binding protein (CREB) [17,35] and CREB as a redox-regulated pathway modulating MnSOD transcription [36], a possible theoretical frame, supporting this proposal, is that high-glucose exposure overexpresses MCR 1,5 and the addition of MCR 1,5 agonists lead to cAMP-PKA-CREB, increasing MnSOD transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Melanocortin receptors (MCR) represent a family of G-proteincoupled receptors classified in five subtypes (MCR [1][2][3][4][5] ) [13][14][15]. MCR are expressed in several tissues including retina [9,16], and they can be activated or inhibited by either agonists as a-melanocyte-stimulating hormone (a-MSH) or antagonists as agouti-related protein [17].…”
Section: Introductionmentioning
confidence: 99%
“…They are expressed in several tissues in man and other mammals. The members of this receptor family are involved in an extraordinarily diverse number of physiological functions, including pigmentation, energy homeostasis, exocrine secretion, inflammation and cardiovascular regulation (Böhm et al., ; Catania, ; Rodrigues et al., ; Slominski et al., ). Even though they are expressed in different cells and tissues, as G‐protein‐coupled receptors, they share the same ancestor pathways: the cAMP/PKA signal pathway and the phosphatidylinositol signal pathway, which do not always necessarily coexist under the same receptor (Collins et al., ; Dennis et al., ; Gilman, ; Irvine, ; Krumins and Gilman, ; Yang, ).…”
Section: Mc1r: a Key Regulator Of Pigmentationmentioning
confidence: 99%
“…For many years, diverse experimental evidence has been contributing to create a ‘biochemical fingerprint of cutaneous phototype’, which does not only include the contribution of melanin . In this respect, the study of MC1R may become extremely interesting, especially if it begins to be considered as more than just ‘the principle regulator of melanogenic enzymes’, but also as a member of the ‘MCR family’, that is a family of receptors which carry out different functions in cells and tissues (Böhm et al., ; Catania, ; Rodrigues et al., ; Slominski et al., ), functions which all produce cellular protection and well‐being. As melanoma susceptibility is often related to the presence of ‘loss‐of‐function’ MC1R variants in some subjects’ genomes, what importance might the presence of one of these variants have in conditioning the response of PPAR‐ γ , or in other aspects of cellular well‐being?…”
Section: Perspectivesmentioning
confidence: 99%
“…151,152 All of the melanocortin peptides are derived from POMC, 12 and have some function in regulating food intake. Our group recently showed that ACTH, and the C-terminal fragment of ACTH, b-celltropin (bCT) have effects on food intake in chicks, with ACTH being anorexigenic, 153 and bCT being orexigenic; 154 the same effects on food intake were reported in rats.…”
Section: Adipose Phyiology: A-mshmentioning
confidence: 99%